Advocate for the doomed : the diaries and papers of James G. McDonald, 1932-1935 - McDonald, James G. (James Grover), 1886-1964 (DIARIES AND PAPERS OF JAMES G. MCDONALD., 2007)
"The private diary of James G. McDonald (1886-1964) offers a unique and hitherto unknown source on the early history of the Nazi regime and the Roosevelt administration's reactions to Nazi persecution of German Jews. Considered for the post of U.S. ambassador to Germany at the start of FDR's presidency, McDonald traveled to Germany in 1932 and met with Hitler soon after the Nazis came to power. Fearing Nazi intentions to remove or destroy Jews in Germany, in 1933 he became League of Nations High Commissioner for Refugees and sought aid from the international community to resettle outside the Reich Jews and others persecuted there. But McDonald met with little success. The lack of international movement on the refugee issue caused him to resign in December 1935 in protest at the lack of support for his work. Not written for publication and never revised, this diary shows McDonald in the 1930s shuttling back and forth among key political and financial authorities in the United States, Germany, Britain, France, Latin America, and the Vatican. A shrewd observer, McDonald meticulously recorded his extraordinary insights into their thoughts and motives. This invaluable, almost day-to-day record of efforts to help increasingly desperate German Jews seeking refuge will fascinate readers interested in this tragic period and will benefit scholars for generations."--Jacket.